Women's economic rights in developing countries and the gender gap in migration to Germany - Eric Neumayer; Thomas Plümper (IZA Journal of Development and Migration, 2021)
There is a large variation across countries of origin in the gender composition of migrants coming to Germany. We argue that women's economic rights in developing countries of origin have three effects on their migration prospects to a place like Germany that is far away and difficult to reach. First, the lower are women's economic rights the fewer women have access to and control over the resources needed to migrate to Germany. Second, the lower are the rights the lower is women's agency to make or otherwise influence migration decisions. These two constraining effects on the female share in migrant populations dominate the opposing third effect that stems from low levels of women's economic rights generating a potentially powerful push factor. We find corroborating evidence in our analysis of the gender composition of migration to Germany over the period 2009-2017.
Keywords: F22; K37; O15; 330; migration; economic rights; gender; resources; agency